Cardiovascular disease and COVID-19: les liaisons dangereuses. (27th August 2020) - Barison, Andrea; Aimo, Alberto; Castiglione, Vincenzo; Arzilli, Chiara; Lupón, Josep; Codina, Pau; Santiago-Vacas, Evelyn; Cediel, Germán; Emdin, Michele; Bayes-Genis, Antoni
Abstract: Patients with cardiovascular risk factors or established cardiovascular disease have an increased risk of developing coronavirus disease 19 and have a worse outcome when infected, but translating this notion into effective action is challenging. At present it is unclear whether cardiovascular therapies may reduce the likelihood of infection, or improve the survival of infected patients. Given the crucial importance of this issue for clinical cardiologists and all specialists dealing with coronavirus disease 19, we tried to recapitulate the current evidence and provide some practical recommendations.